Increased insulin-like growth factor 1 concentrations in a retrospective population of non-diabetic cats diagnosed with hypertrophic cardiomyopathy. Issue 10 (October 2021) - Steele, Matthew ME; Borgeat, Kieran; Payne, Jessie R; Coss, Peter; Navarro-Cubas, Xavier; Church, David B; Niessen, Stijn JM; Connolly, David J
Objectives: The aim of the study was to document whether a proportion of non-diabetic cats with left ventricular hypertrophy (LVH) previously diagnosed with hypertrophic cardiomyopathy (HCM) have elevated circulating insulin-like growth factor 1 (IGF-1) concentrations. Methods: A retrospective analysis of residual blood samples obtained at the time of echocardiographic diagnosis of HCM from a population of 60 non-diabetic cats were analysed for circulating IGF-1 concentrations using a validated radioimmunoassay and compared with a control group of 16 apparently healthy cats without LVH. Clinical and echocardiographic data for cats with an IGF-1 level >1000 ng/ml were compared with those with an IGF-1 level <800 ng/ml. Results: In total, 6.7% (95% confidence interval 1.8–16.2%) of cats with HCM had an IGF-1 level >1000 ng/ml. The prevalence of an IGF-1 level >1000 ng/ml in the control group was zero. Conclusions and relevance: A small proportion of non-diabetic cats previously diagnosed with HCM had an IGF-1 concentration at a level that has been associated with feline hypersomatotropism (fHS) in the diabetic cat population. Further prospective research is required to confirm or refute the presence of fHS in non-diabetic cats with LVH and increased IGF-1.